2021
DOI: 10.1155/2021/9918763
|View full text |Cite
|
Sign up to set email alerts
|

Biometry, Refractive Errors, and the Results of Cataract Surgery: A Large Sample Study

Abstract: The statistical characteristics of biometry and refractive error in a large sample of cataractous Cuban patients are presented, comparing between sexes and age groups. All patients were studied at the Cuban Institute of Ophthalmology “Ramón Pando Ferrer,” La Habana. The sample consists of 28252 eyes of 25068 patients, subjected to cataract surgery during the time period between 2006 and 2019. Their biometry was obtained using IOL Master devices; also, visual acuity, refraction, and corneal power were registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…A unique aspect of this study was acquiring ACD measurements by two different instruments. The IOL Master 500 an ophthalmic biometer based on partial coherence interferometry [26] and the IOL Master 700 is an ophthalmic biometer based on swept source optical coherence tomography [27]. The UBM technique, developed by Pavlin et al [28], can provide images of the biometric and quantitative assessments of the ocular biometric parameters [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…A unique aspect of this study was acquiring ACD measurements by two different instruments. The IOL Master 500 an ophthalmic biometer based on partial coherence interferometry [26] and the IOL Master 700 is an ophthalmic biometer based on swept source optical coherence tomography [27]. The UBM technique, developed by Pavlin et al [28], can provide images of the biometric and quantitative assessments of the ocular biometric parameters [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent study demonstrated the importance of histometric data from the cornea in patients before cataract surgery. 12 On the other hand, the width measurement of keratinized gingiva, supracrestal gingival tissue, sulcus depth, and biological width has been demonstrated. 13 The results of this study explain that histometrics is needed for diagnosis.…”
Section: Editorialmentioning
confidence: 99%
“…1 B), and optic disk size is used in the assessment and diagnosis of glaucoma patients. 5 , 6 However, as these images are formed by light rays that pass through the lens and cornea, changes in their optical properties will result in differences in magnification of fundus images, 7 as illustrated in Figure 1 C. As a result, fundus photographs cannot be used for accurate distance measurements, unless they are corrected for these optical effects.…”
mentioning
confidence: 99%